2008
DOI: 10.1007/s11608-008-0192-y
|View full text |Cite
|
Sign up to set email alerts
|

Sensations éjaculatoires chez l’homme paraplégique et tétraplégique durant la stimulation par vibromassage avec et sans Gutron®

Abstract: Depuis les travaux sur l'utilisation du Gutron ® en Europe et au Canada (Québec), nous avons étudié les sensations somatiques et autonomiques pouvant être associées à l'éjaculation chez les hommes blessés médullaires. Puisque l'éjaculation est associée à une activité sympathique, que le Gutron ® est un alphastimulant et que l'activité sympathique peut être transmise par divers circuits nerveux, nous avons émis l'hypothèse que l'éjaculation serait associée à des perceptions autonomiques malgré les lésions. Un t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…The results of the present study on the use of midodrine combined with vibrostimulation further support the effectiveness of the drug, an α stimulating molecule, to increase ejaculation success in men with SCI [3,12,17,41–45]. Surprisingly however, the data revealed fewer sensations when midodrine was combined with vibrostimulation as opposed to when vibrostimulation was used alone.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The results of the present study on the use of midodrine combined with vibrostimulation further support the effectiveness of the drug, an α stimulating molecule, to increase ejaculation success in men with SCI [3,12,17,41–45]. Surprisingly however, the data revealed fewer sensations when midodrine was combined with vibrostimulation as opposed to when vibrostimulation was used alone.…”
Section: Discussionsupporting
confidence: 76%
“…[17], who suggested that midodrine increases both the ejaculation success and the orgasmic potential of men with SCI. It may be that midodrine lowers the threshold for ejaculation through its sympathetic effect [37,45], but that it is the ejaculation itself that is responsible for the climactic sensations [45,46]. It is also possible that midodrine, especially at higher doses, triggers side effects that become disruptive to the overall perception of climax.…”
Section: Discussionmentioning
confidence: 99%